Rancang Bangun Aplikasi Chatbot Sebagai Bentuk Pelayanan Prima Untuk Penerimaan Mahasiswa Baru - Murhadi Murhadi (INTEK : Jurnal Informatika dan Teknologi Informasi, 2019)
Excellent service is the best form of service to consumers to feel satisfied. The purpose of excellent service is that consumers or prospective consumers feel underserved and in terms of agencies or companies will increase consumer confidence. Muhammadiyah University Purworejo (UMP) as an educational institution has prospective consumers, namely the millennial generation. The habit of the millennial generation in accessing information is by digitally searching. To access more detailed information, they are accustomed to asking through the texting method via chat. Therefore, the University needs to provide a texting application that can answer questions anytime and with a short reply time.The chat application developed in the form of chatbots.The chat-bot application development begins with studying general questions that are often asked by prospective students. The combination of question words and keywords from each question. From the keywords that are prepared an automatic answer that contains information that the prospective student wants to access. In addition, in each answer a key for information related information will be provided. The results of the design and development of the Chatbot application, namely the implementation of Chatbot can be used as a substitute for the role of humans in providing excellent service. This chatbot can provide quick and complete answers. In terms of the excellent service factor, this Chatbot can fulfill the attitude, attention, action, ability and accountability factors.